Improved Dynamics of Thoracic Cage and Exercise Capacity after Nuss Repair for Pectus Excavatum - Yeh, Shu-Wei; Yang, Mei-Chen; Chang, Yi-Wei; Hsu, Yu-Ting; Tzeng, I-Shiang; Cheng, Yeung-Leung (The Thoracic and Cardiovascular Surgeon, 2020)
Background Pectus excavatum (PE) reduces the dynamics of the thoracic cage, with a negative impact on exercise capacity. We aimed to evaluate the effects of Nuss repair for PE on the dynamics of the thoracic cage and exercise capacity in adults.Methods This was a prospective observational study of 46 adults (mean age, 26.2 years) who underwent PE correction using the Nuss procedure between September 2016 and August 2017. Cirtometry was used to obtain measures of thoracic cage circumference at two levels (axillary level [AL] and xyphoid level [XL]), at the end points of inspiration and expiration. Circumference measures were obtained before surgery and at 1, 3, and 6 months after surgery. Exercise capacity was also evaluated using the 6-minute walk test (6MWT). The association between the 6MWT data and cirtometry measures was evaluated using Pearson's correlation.Results The circumference at maximum inspiration increased from baseline to 3 months after surgery (p < 0.01), at both the AL (84.5 ± 4.9 vs. 88.5 ± 5.1 cm) and XL (80.1 ± 4.8 vs. 83.7 ± 5.1 cm). The 6MWT also significantly improved from baseline to 3 months after surgical correction (544.7 ± 64.1 vs. 637.3 ± 59.4 m, p < 0.01), with this improvement being correlated to the increase in thoracic circumference on maximal inspiration at both the AL and XL (0.8424 and 0.7951, respectively).Conclusion Improved dynamics of the thoracic cage were achieved after Nuss repair for PE in adults. This increase in thoracic circumference at maximum inspiration was associated with an improvement in exercise capacity at 3 months after surgery.
Keywords: pectus excavatum; Nuss procedure; thoracic cage; cirtometry; 6-minute walk test